Study of relationship between ABO & Rh Blood group and Type 2 Diabetic Mellitus - Basak Asim Kumar; Maji Kaushik (International Journal of Medical Research and Review, 2016)
Background & Objective: The findings of Arid et al, in 1953 regarding association between carcinoma of stomach and B blood group and successively in 1954 regarding association between peptic ulcer and O blood group opened a new approach to find association of blood group with other commonly occurring diseases. But there are conflicts of reports regarding association between diabetic mellitus (DM) (Type 2 ) and blood groups. Therefore the present study aims to find out whether there is any association between blood group and Type 2 diabetes mellitus.Methods: For this study diabetic patients of both sexes of Haldia and Tamluk subdivision reported in our associated Dr. B. C. Roy Hospital, Haldia are considered. The ABO blood group and Rh factor of both the groups were determined using the Tile or Slide testing method and the frequency of occurrence of ABO & Rh blood group among diabetic & non diabetic population was assessed. The frequency distribution of ABO blood group and Rh factor among the entire DM population was compared with that of general non diabetic population by Chi Square test.Result: The present study indicates that neither the frequency distribution of ABO group nor the Rh factor of diabetic subjects significantly differs from the non diabetic (control) group.Conclusion: The present study suggests that there might have no association between ABO blood group and Rh factor with diabetes mellitus.